Makna Pengulangan Ayat dalam al-Qur’an Surah ar-Rahman: Tinjauan Literatur - Ahmad Syawal; Faizah Binti Awad; Nurdin; Muh. Ikhsan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the meaning of repetition of verses in surah ar-Rahman. This study uses a qualitative approach with a descriptive-analytical method. The formal object of this research is the analysis of interpretation, while the material object is the repetition of verses in Surah ar-Rahman. The results and discussion of this study indicate that the meaning of the repetition of Surah ar-Rahman includes stylistically not as tauqid but taqrir al-ma'na, meaning the balance of the heavens and the universe, the command to be grateful for favors, so that humans enjoy the beauty of language style, and related to the nature of ar-Rahman. This study concludes that the repetition of verses in Surah ar-Rahman has a lot of meaning, leaving it to the commentators who dig into its unlimited depth. This study recommends that enthusiasts of the study of the Qur'an and Tafsir be able to explore the meaning of the repetition of verses in Surah Ar-Rahman which is very abundant for the enlightenment of Muslims in living their daily lives.